Fungal endophthalmitis: an unusual complication of GI surgery and endoluminal vacuum therapy. (23rd July 2015) - Wood, Megan; Wright, David; Witherspoon, Paul
Abstract : We present a case of endogenous fungal endophthalmitis arising as a complication of fungal septicaemia following gastrointestinal surgery, and subsequent treatment with endoluminal vacuum therapy (Endo-SPONGE, B Braun Medical Ltd). Our patient developed a pre-sacral collection due to an anastomotic leak post ileoanal pouch formation. Despite treatment with Endo-sponges and antibiotics, the patient suffered recurrent sepsis and the cavity failed to reduce in size. He developed red eyes and blurred vision, leading to the diagnosis of fungal endophthalmitis. Extended fungal cultures of the Endo-sponges and pouch effluent revealed Candida spp. This case is the first report of fungal endophthalmitis associated with Endo-sponge use and highlights the importance of fungal cultures in patients with ongoing sepsis.